1997
DOI: 10.1056/nejm199710163371601
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 2 in the United States, 1976 to 1994

Abstract: Since the late 1970s, the prevalence of HSV-2 infection has increased by 30 percent, and HSV-2 is now detectable in roughly one of five persons 12 years of age or older nationwide. Improvements in the prevention of HSV-2 infection are needed, particularly since genital ulcers may facilitate the transmission of the human immunodeficiency virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
372
4
14

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,078 publications
(420 citation statements)
references
References 36 publications
30
372
4
14
Order By: Relevance
“…The epidemic of genital herpes continues to increase in the U.S.; ϳ22% of adults are infected with HSV-2, representing a 31% increase over the last decade (1). After primary infection at mucosal sites, HSV-2 remains latent in neuronal cells with intermittent HSV reactivations, resulting in the production of infectious virus with or without the onset of discernible disease.…”
mentioning
confidence: 99%
“…The epidemic of genital herpes continues to increase in the U.S.; ϳ22% of adults are infected with HSV-2, representing a 31% increase over the last decade (1). After primary infection at mucosal sites, HSV-2 remains latent in neuronal cells with intermittent HSV reactivations, resulting in the production of infectious virus with or without the onset of discernible disease.…”
mentioning
confidence: 99%
“…The incidence of genital herpes infections caused by HSV-1 and 2 has increased significantly in the past 20 years (Fleming et al, 1997). Since the introduction of antiviral drugs in the early 1980s (Balfour, 1999), the management of genital herpes infections has improved considerably although it is not yet possible to cure herpes virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 HSV infection at birth may result from in utero exposure or may present later in the neonatal period as a result of perinatal or postnatal exposure. 1 It was previously demonstrated that for HSV infection acquired around the time of birth, the risk of neonatal HSV depends upon: (1) the viral load to which the infant is exposed, regardless of whether the mother has genital lesions with active shedding of HSV or is shedding asymptomatically; (2) maternal HSV infection/immunity status; 1,8,9 and (3) laceration of neonate's skin at the time of delivery by using an invasive technique such as scalp electrode and/or vacuum extraction for assisted delivery.…”
Section: Discussionmentioning
confidence: 99%